Experimental investigation of friction behavior in pre-sliding regime for pneumatic cylinder - Bo, Tran Xuan; Thang, Pham Tat; Cong, Do Thanh; Loc, Ngo Sy (Vietnam Journal of Mechanics, 2014)
Friction always presents in pneumatic cylinders and causes difficulties in controlling position and velocity of pneumatic systems. In order to improve the control performance of the pneumatic systems, it is necessary to fully understand behavior of friction in the pneumatic cylinders. So far, dynamic friction behavior of pneumatic cylinders has been investigated but mainly focused on the friction behavior in sliding regime. In pre-sliding regime, friction behavior has not been investigated. In this paper, experimental investigations of friction behavior of a pneumatic cylinder in pre-sliding regime are made. The friction force is calculated from the equation of motion of the piston using the measured values of pressures in the two cylinder chambers and the piston displacement. The pressures are controlled by using two proportional pressure control valve. The friction force versus piston displacement characteristics are measured and analysed under various operating conditions of the applied force and the pressures. Experimental results show that: i) the piston motion in pre-sliding regime exhibits a nonlinear spring behavior; ii) hysteretic behavior with nonlocal memory is verified; iii) the pressures have influence only on the size of the hysteretic loop. These experimental results can be applied to develop a friction model for pneumatic cylinders.